IDENTIFIKASI EKTOPARASIT DAN PREVALENSI PADA IKAN BANDENG (Chanos chanos) DI TAMBAK CINTA RAJA, KOTA LANGSA ABSTRAK - Mauliza, Ria; AS, Agus Putra; Komariyah, Siti (JURNAL PERIKANAN TROPIS, 2025)
Milkfish (Chanos chanos) is a brackish water fish that is a popular as food in Southeast Asia and Oceania. Milkfish has a high economic value with relatively competitive prices. As the milkfish cultivation business develops in the ponds of Cinta Raja Village, several problems can hinder its progress, one of which is disease caused by parasites. Therefore, the aim of this research is to identify and determine the prevalence level of ectoparasites in milkfish at the Cinta Raja pond, Langsa City. This research was conducted using a survey menthod, with sampling carried out purposively. Sampling was collected at the Cinta Raja Pond in Langsa City from September 18 to October 10, with a total of 90 samples taken. Sampling was conducted 9 times. The fish sampled were 2 months old. Ectoparasite identification was performed at the Agrotechnology Laboratory, Faculty of Agriculture, Samudra University. The results of this study identified four types of ectoparasites infecting milkfish, namely Dactylogyrus sp. (22.23%), Trichodina sp. (20%), Unitubulotestis sp. (13.4%), with Dactylogyrus sp. being the most common parasite, infecting 258 milkfish samples.Keywords: Ectoparasites, Milkfish, Dactylogyru, Aquaculture